The Value of Moral Education Based on Local Wisdom in Pappaseng To Riolo - Ahmad Abu Rizki; Khasani, Fahim; Firman; Haikal Ramadhan, Narendra Jumadil; Nurhidayah (Al-Ishlah: Jurnal Pendidikan Islam, 2024)
Background: Islamic education primarily derives from the Quran and hadith. However, other sources, including madzhab sahabi, maslahah mursalah, ijtihad, and urf (local wisdom), also contribute to its development. One example of local wisdom aligned with Islamic teachings is the Bugis tribe's pappaseng to riolo (ancestral advice). Research Objectives: : This study aims to analyze the moral education values embedded in pappaseng to riolo, focusing on its relevance to Islamic teachings. Methods: This research adopts a library research approach, utilizing content analysis techniques. Data is sourced from the book Traditional Messages (Pappaseng To Riolo) by Nonci, alongside other relevant references. Conclusions: The findings highlight the importance of local wisdom as a complementary source of Islamic education, particularly in moral education. The value of local wisdom-based moral education contained in pappaseng to riolo lies in its emphasis on moral education to Allah SWT and interpersonal relationships among humans. This underscores the significance of integrating cultural heritage into educational frameworks and calls for further exploration of similar local wisdom traditions. Keywords: moral education; local wisdom; Bugis tribe; pappaseng to riolo; Islamic education